USAGE OF OLICARD-40-RETARD IN TREATMENT OF PATIENTS WITH UNSTABLE ANGINA - A. L. Rakov; V. L. Yanshin (Российский кардиологический журнал)
Usage of olicard-40-retard in treatment of patients with unstable angina.